COMPARISON OF PORTERS STEMMING ALGORITHM AND NAZIEF & ADRIANI'S STEMMING ALGORITHM IN DETERMINING INDONESIAN LANGUAGE LEARNING MODULES - Tuhpatussania, Siti; Utami, Ema; Hartanto, Anggit Dwi (Jurnal Pilar Nusa Mandiri, 2022)
One of the methods used to improve the performance of text summarization to obtain complete information in a learning module is by transforming the words in a module into basic words or, in other words, through a steaming process. The steaming process in Indonesian language texts is more complicated/complex because there are word affixes that must be removed to get the root word (root word) of a word, so this research will compare the two stemming algorithms of Porter and stemming Nazief & Adriani in the learning module at Mataram University of Technology. The test results of the Nazief & Adriani stemming algorithm on an average process duration of 51.8 seconds with an average accuracy of 74.175%. In Porter's Algorithm, the average processing time is 16.875 seconds, with an accuracy of 73.225%.